Reconstruction Discourse Justice Criminal Law as an Ideal Model for Implementing Restorative Justice - Satria Dwie Raharja; Ade Saptomo (Riviera Publishing, 2024)
T The criminal justice system in Indonesia faces various challenges, including legal inefficiency, high recidivism rates, and inadequate victim protection. The punishment-oriented system often neglects the need for victim recovery and social recovery. This study aims to develop an ideal model for implementing restorative justice within the Indonesian legal framework by considering the principles of customary law that have long been practiced in society. This study uses a normative legal approach by analyzing legislation, literature studies, and comparative assessments of restorative justice practices in various countries. Primary and secondary legal materials are used to explore the application of restorative justice at the police, prosecution, and court levels. The findings reveal several barriers to implementing restorative justice in Indonesia, such as regulatory misalignment across law enforcement agencies, limited human resource training, and lack of public awareness. However, the study highlights significant potential for adopting the restorative justice model through integrating local values, law enforcement training, and a comprehensive regulatory framework. The implications of this study emphasize the need for more inclusive policy reforms, strengthening collaboration between legal institutions, and public education to increase the acceptance of restorative justice as an alternative method of resolving criminal cases. Proper implementation is expected to create a more just, more humane, and socially restorative legal system.